Effect of heat stress on developmental stages, yield and fibre traits of cotton (Gossypium hirsutum) - Kanwal, Sadia; Shahid, Muhammad Rafiq; Nazir, Wajid; Khan, Muhammad Usama; Hussain, Nadia; Bibi, Amna; Farooq, Muhammad; Muhammad, Taj; Ramzan, Muhammad (Journal of Pure and Applied Agriculture, 2023)
Cotton is taken as white gold for the economy of Pakistan. However, heat stress is the most crucial factor that drastically affects its yield right from germination to maturity. Optimum temperature for root development is 30-35°C but at 40°C root development stops. Extremes of high temperature are harmful that hinders the photosynthetic rate of the crop. For fruiting 27-32°C temperature is required but an increase in temperature from optimum range reduces time for synthate accumulation resulting in fruit shedding. Higher temperature stress decreases pollen viability and the anther indehiscence, which results in a lower seed setting rate and causes significant reductions in final yield. At 40°C Rubisco activity is also inhibited thus results in photosynthesis hindrance. In the case of the cotton crop, an increase in 1°C of temperature, 110kg/ha lint yield is reduced. Heat stress along with water stress also affects potassium and soluble sugar that contribute 80% of total fiber sap resulting in the shortening of fiber length. High temperature can cause roughness of fiber, increasing the micronaire of lint. Lint index, lint percentage, and lint per boll decreased when temperature exceeds 37°C. Therefore, this review article demonstrates the effects of heat stress on different crop stages, productivity, and fiber quality of cotton. Cotton breeders should focus on development of climate resilient cultivars of cotton. © 2021 Department of Agricultural Sciences, AIOU